COLLABORATION BETWEEN ACADEMICS AND LOCAL GOVERNMENTS IN PREPARING POLICIES TO Ease Doing Business for MSMEs IN THE RIAU ISLANDS - Ngaliman; Bambang Satriawan; Edi Indera; Sri Yanti (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
One constraint for business micro small And medium enterprises (SMEs) in start And develop business is lack of convenience effort given​ government in various form its policies . Ease try start from availability information related opportunity business , HR training , fiscal incentives in form loan cost cheap until related marketing the product . In Effort For push development of MSMEs in the Province Riau Islands Academics University Batam ( Uniba ) and Government Province Riau Islands via Service Investment and​ Service Integrated One The door (DPMPTSP) makes an agenda for formulate convenience business that can given all OPDs against MSME actors . Results identification convenience business That will made into material for Provincial Government Riau Islands For make Design Regional Regulations that can give convenience to public Riau Islands in MSME sector . Regulation required Government Province Riau Islands can brave And No doubtful in give convenience try MSME actors according to his authority . Service Investment and​ Service Integrated One Door (DPMPTSP Together with the Academic Team Uniba do visit to a number of office Department / Agency Government at the level province For collect empirical data , and activities that have been they do during This in developing MSMEs. There is around 114 thousand more MSMEs in Kepri.They face a number of challenges , including is expensive logistics And infrastructure . As region islands , MSMEs face uncertainty transportation sea , infrastructure minimal ports , as well as expensive fare send , which increases cost operational . In addition that , they face competition with product outside a larger country cheap , especially through e-commerce, threatening sustainability product local . Capital issues and access financing Also become obstacles . Many MSMEs have difficulty get formal financing because limitations guarantee .